The biblical view of humanity and the promotion of the rights of persons with disabilities: the call and mission of the church - P. White (Acta Theologica)
It is estimated that 10 per cent of the world’s population, approximately 650 million people live with disability. Eighty per cent of them live in developing countries. The needs and rights of persons with disabilities have been high on the United Nations agenda for at least three decades. This concern of the United Nations raises the question of the missional role of the church in addressing the spiritual, social and emotional needs of people with disabilities. “Speak up for those who cannot speak for themselves, for the rights of all who are destitute” (Prov. 31:8). In this light, the article discusses the missional role of the church in promoting the rights of people with disabilities, by engaging literature on disability, the rights of people with disability, the biblical view of humanity, and the missional agenda of the church from an ecumenical and theological perspective. The article concludes that the church has a missional call to serve as the home and prophetic voice for the marginalised in society.